2023
DOI: 10.7759/cureus.33272
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Dried Red Jujube Fruit Extract Against Acetaminophen-Induced Acute Hepatotoxicity

Abstract: Background A liver injury could impair the integration of the body’s organ system, which may cause complications that can lead to death. The dried red jujube fruit extract has the potential to protect the liver from toxic substances through its antioxidant properties. Aims To determine and analyze the hepatoprotective effect of dried red jujube fruit extract on aminotransferase levels against acetaminophen-induced acute hepatotoxicity. Methods Male Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…5,16,26 In osteoarthritis, intraarticular injections of HA and other PG-containing mixtures are used to provide temporary relief of joint pain, but the clinical benefit is modest and of short duration. [195][196][197] The age-related changes in PGs and other ECM components that occur during aging may be due, in part, to changes in the activity of certain enzymes, such as MMPs, which can degrade the ECM as discussed above. In addition, aging is associated with decreases in the biosynthetic activity and turnover of cells such as tenocytes, fibroblasts, and chondrocytes that produce and maintain the ECM and its PGs.…”
Section: Pgs and The Mechanical Aspects Of Agingmentioning
confidence: 99%
“…5,16,26 In osteoarthritis, intraarticular injections of HA and other PG-containing mixtures are used to provide temporary relief of joint pain, but the clinical benefit is modest and of short duration. [195][196][197] The age-related changes in PGs and other ECM components that occur during aging may be due, in part, to changes in the activity of certain enzymes, such as MMPs, which can degrade the ECM as discussed above. In addition, aging is associated with decreases in the biosynthetic activity and turnover of cells such as tenocytes, fibroblasts, and chondrocytes that produce and maintain the ECM and its PGs.…”
Section: Pgs and The Mechanical Aspects Of Agingmentioning
confidence: 99%
“…Paracetamol (acetaminophen) is an NSAID that, for an acute overdose, could cause hepatotoxicity manifested with hepatic glutathione depletion, significant oxidative stress, and inflammatory effects [122]. Recent findings revealed that various plant extracts reduced paracetamol-induced toxicity through hepatoprotective and antioxidant activity mechanisms [123]. Likewise, oak galls showed promising results.…”
Section: In Vivo Activitymentioning
confidence: 99%